Influence of Process Parameters on Kerf Width in Abrasive Waterjet Machining of GFRP Composites - Kaptan, Arslan; Mercan, Serdar; Kartal, Fuat (Cumhuriyet University, 2024)
This study investigates the influence of process parameters on kerf width in abrasive waterjet (AWJ) machining of glass fiber reinforced polymer (GFRP) composites. The experimental analysis was conducted using a Taguchi L27 orthogonal array to optimize the machining parameters: pressure, feed rate, abrasive flow rate, and standoff distance. The top kerf width (TKW) and bottom kerf width (BKW) were measured to evaluate the impact of these parameters. Results indicate that higher pressures and abrasive flow rates generally increase both TKW and BKW due to enhanced material removal rates. Conversely, increased feed rates tend to reduce kerf widths, highlighting the importance of optimizing cutting speeds. Standoff distance exhibited a less pronounced effect but still influenced the kerf widths. The optimal parameters for minimizing TKW and BKW were identified, providing valuable insights for improving precision and efficiency in AWJ machining of GFRP composites. These findings contribute to the development of more effective manufacturing practices for high-performance composite materials.
Keywords: Material Design and Behaviors; Abrasive waterjet cutting; Aşındırıcı su jeti kesimi; optimizasyon; takviyeli kompozit; GFRP; işleme parametreleri; kesme genişliği.; Malzeme Tasarım ve Davranışları; reinforced composite; GFRP; kerf width.; machining parameters; optimization; Abrasive waterjet cutting; optimization; reinforced composite; GFRP; machining parameters; kerf width.